Study of clinical polymorphism and the quality of life of patients with essential tremor - Iu. V. Iarygina; D. V. Zaharov; V. A. Mikhailov; V. A. Bogacheva; L. A. Hublarova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Essential tremor (ET) is characterized by heterogeneity and variable intensity of hand tremor, which accounts for the severity of functional disorders, thus lowering the quality of life (QoL) of patients. Findings: As a result of the research, we have identified subgroups of essential tremor characterized by significant variability of the tremor amplitude and duration. The first subgroup has kinetic tremor prevailing over postural tremor, predominantly asymmetric; the second subgroup is represented by high-amplitude symmetric posture-kinetic tremor; the third group has low-amlitude posture-kinetic tremor. Tremor mostly limits role activity with relative preservation of the ability to perform general physical exercise. Patients with ET are defined by medium and low estimate of physical and mental components of the QoL. The QoL was estimated lowest by the patients of subgroup 2, whereas the health physical component was higher in patients of group 3 which was complemented by a shorter duration of tremor.